Room for improvement in nutrition knowledge and dietary intake of male football (soccer) players in Australia - Andrews, M. C.; Itsiopoulos C. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Athletes require sufficient nutrition knowledge and skills to enable appropriate selection and consumption of food and fluids to meet their health, body composition, and performance needs. This article reports the nutrition knowledge and dietary habits of male football (soccer) players in Australia. Players age 18 years and older were recruited from 1 A-League club (professional) and 4 National Premier League clubs (semiprofessional). No significant difference in general nutrition knowledge (GNK; 54.1% ± 13.4%; 56.8% ± 11.7%; M ± SD), t(71) = -0.91, p = .37, or sports nutrition knowledge (SNK; 56.9% ± 15.5%; 61.3% ± 15.9%), t(71) = -1.16, p = .25) were noted between professional (n = 29) and semiprofessional (n = 44) players. In general, players lacked knowledge in regard to food sources and types of fat. Although nutrition knowledge varied widely among players (24.6-82.8% correct responses), those who had recently studied nutrition answered significantly more items correctly than those who reported no recent formal nutrition education (62.6% ± 11.9%; 54.0% ± 11.4%), t(67) = 2.88, p = .005). Analysis of 3-day estimated food diaries revealed both professionals (n = 10) and semiprofessionals (n = 31) consumed on average less carbohydrate (3.5 ± 0.8 gC/kg; 3.9 ± 1.8 gC/kg) per day than football-specific recommendations (FIFA Medical and Assessment Research Centre [F-MARC]: 5-10 gC/kg). There was a moderate, positive correlation between SNK and carbohydrate intake (n = 41, p = 0.32, p = .04), indicating that players who exhibited greater SNK had higher carbohydrate intakes. On the basis of these findings, male football players in Australia would benefit from nutrition education targeting carbohydrate and fat in an attempt to improve nutrition knowledge and dietary practices.